Check the complete question attached.
We have the equation [tex]C= \frac{5}{9} (F-31)[/tex] equation (1); solving for F we get:
[tex] \frac{9}{5} C=F-31[/tex]
[tex]F= \frac{9}{5} C+31[/tex]
[tex]F= \frac{9}{5} (C+31)[/tex] equation (2)
I. To check this we are going to use equation (1) to see what hapen when temperature rises from 32 Fahrenheit to 33 Fahrenheit:
For 32 Fahrenheit:
[tex]C= \frac{5}{9} (32-31)[/tex]
[tex]C= \frac{5}{9} (1)[/tex]
[tex]C= \frac{5}{9} [/tex]
For 33 Fahrenheit:
[tex]C= \frac{5}{9} (33-31)[/tex]
[tex]C= \frac{5}{9} (2)[/tex]
[tex]C= \frac{10}{9} [/tex]
Now we are going to subtract the two temperatures in degrees Celsius:
[tex] \frac{10}{9} - \frac{5}{9} = \frac{5}{9} [/tex] As you can see, the temperature increased [tex] \frac{5}{9} [/tex] degree Celsius.
We can conclude that a temperature increase of 1 degree Fahrenheit is equivalent to a temperature increase of [tex] \frac{5}{9} [/tex] degree Celsius.
II. To check this one we are going to use equation (2) to see what happens when temperature raises from 1 degree Celsius to 2 degrees Celsius:
For 1 degree Celsius:
[tex]F= \frac{9}{5} (C+31)[/tex]
[tex]F= \frac{9}{5} (1+31)[/tex]
[tex]F= \frac{9}{5} (32)[/tex]
[tex]F=57.6[/tex]
For 2 degrees Celsius:
[tex]F= \frac{9}{5} (C+31)[/tex]
[tex]F= \frac{9}{5} (2+31)[/tex]
[tex]F= \frac{9}{5} (33)[/tex]
[tex]F=59.4[/tex]
Now we are going to subtract the two temperatures in Fahrenheit:
[tex]59.4-57.6=1.8[/tex] As you can see, the temperature increased 1.8 Fahrenheit.
We can conclude that a temperature increase of 1 degree Celsius is equivalent to a temperature increase of 1.8 Fahrenheit.
III. Since a temperature increase of 1 degree Fahrenheit is equivalent to a temperature increase of [tex] \frac{5}{9} [/tex] degree Celsius, we can conclude that this one is false.
The correct answer is D) I and II only